Effects of socioeconomic status on academic performance in primary school: A systematic review on the mediating role of executive functions - López Terrones, Marjory C. (2022)
The contribution of executive functions (EF) in the academic achievement gaps associated with socioeconomic status (SES) has been a recurring research topic, especially during the preschool stage; However, it is not so frequent during primary training, taking into account that the EF have a late development and a potential plasticity during this period that make them sensitive to the experiences of the environment. For this reason, the present review aimed to analyze research related to the mediating role of the EF in the effects of the SES on academic achievement in primary school children. In addition, it is important to know the differential contribution of each component of the executive functions to academic achievement and if there are differences in the magnitude of the mediation when mathematics is separated from reading. Lastly, to confirm that EF have a particular and fundamental role in reducing the negative effects of SES on academic achievement, the participation of other cognitive factors as mediator candidates is evaluated. Our results inform that the EF, measured during the preschool and primary period, continue to be a robust mediator of later academic performance. Working memory obtains the most consistent and robust results compared to the rest of the EF. There are differences in the magnitude of the mediation when the academic domains are separated, but there are cultural and ethnic aspects that intervene in the results. In general, the mediating effects of other cognitive factors vary when analyzed together with the EF.